2020
DOI: 10.1101/2020.06.10.144337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intraspecific diversity loss in a predator species alters prey community structure and ecosystem functions

Abstract: Loss in intraspecific diversity can alter ecosystem functions, but the underlying mechanisms are still elusive, and intraspecific biodiversity-ecosystem function relationships (iBEFs) have been restrained to primary producers. Here, we manipulated genetic and functional richness of a fish consumer (Phoxinus phoxinus), to test whether iBEFs exist in consumer species, and whether they are more likely sustained by genetic or functional richness. We found that both genotypic and functional richness affected ecosys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Intra-species variation has been demonstrated to have great impact on species coexistence (Hart, Turcotte & Levine 2019), consumer-resource dynamics (Raffard et al . 2021) and receives increasing attention in biodiversity-ecosystem functioning studies (Violle et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-species variation has been demonstrated to have great impact on species coexistence (Hart, Turcotte & Levine 2019), consumer-resource dynamics (Raffard et al . 2021) and receives increasing attention in biodiversity-ecosystem functioning studies (Violle et al .…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that soil bacteria alter the outcome of these plant-aphid interactions, and it is possible that this occurs through altering the ability of the aphids to alter local plant physiology to their benefit; however, this also remains to be tested. Intra-species variation has been demonstrated to have great impact on species coexistence (Hart, Turcotte & Levine 2019), consumer-resource dynamics (Raffard et al 2021) and receives increasing attention in biodiversity-ecosystem functioning studies (Violle et al 2012;Whitham et al 2020). Our experiment indicated that mixed aphid genotype populations resulted in variable shoot damage across plant varieties compared to the single genotype treatment dependent on soil bacteria inoculation, and interactions among the aphid-suppressing bacteria treatment and between aphid genotypes altered aphid growth rates with consequences for aphid rapid evolution in the mixed populations.…”
Section: Discussionmentioning
confidence: 99%
“…BEF relationships have been historically described at theinterspecific level, and seminal experiments have demonstrated that higher plant species richness in communities increases and stabilises yields (Tilman et al1996(Tilman et al , 2006Chapin et al 1997). More recently, similar observations have been reported at the intraspecific level; plant or animal populations composed of a large number of genotypes sustain higher yields and community diversity than populations with a poor genotypic diversity (e.g., Hughes & Stachowicz 2004;Reusch et al 2005;Crutsinger et al2006;Raffard et al 2021). Altogether, this suggests that both losing alleles within populations and species within communities can alter the functioning of ecosystems.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, despite its potential direct effects on fitness (Hansen et al, 2009; Lamaze et al, 2012; Morissette et al, 2018), stocking may have significant effects on spatial patterns of genetic diversity and differentiation, even when it ceased many generations ago (Hansen et al, 2009; Marie, Bernatchez & Garant, 2010; De Santis et al, 2021). For example, modifying the spatial or temporal structure of populations can profoundly influence local food webs, with subsequent ecological consequences through community structure of invertebrate prey and primary productivity (Harmon et al, 2009; Cucherousset & Olden, 2020; Raffard et al, 2021) or through non‐trophic effects (Whitham et al, 2003; Matthews et al, 2011). In addition, the potential disappearance of conservation units of high interest for the representation and persistence of diversity is another conundrum posed by stocking (Antunes et al, 2001; Moritz, 2002; Ferguson, 2004).…”
Section: Conclusion and Conservation Implicationsmentioning
confidence: 99%